ANALISIS KEMAMPUAN MEMBACA PERUMULAAN PADA PESERTA DIDIK KELAS II SD GMIT 006 OA - Hermolinda Leng; Trisnawazti Y. Daik; Halena Muna Bekata (STKIP Subang, 2026)
This study aims to describe the beginning reading skills of second-grade students at SD GMIT 006 OA. The study used a descriptive qualitative method involving 25 students. Data were collected through observation and reading tests. The results indicate that students still experience difficulties in recognizing consonants, distinguishing similar letters, reading syllables, words, simple sentences, and understanding reading texts. The findings imply the need for intensive guidance from teachers and parents and regular reading practice.This study aims to describe the beginning reading skills of second-grade students at SD GMIT 006 OA. The study used a descriptive qualitative method involving 25 students. Data were collected through observation and reading tests. The results indicate that students still experience difficulties in recognizing consonants, distinguishing similar letters, reading syllables, words, simple sentences, and understanding reading texts. The findings imply the need for intensive guidance from teachers and parents and regular reading practice.This study aims to describe the beginning reading skills of second-grade students at SD GMIT 006 OA. The study used a descriptive qualitative method involving 25 students. Data were collected through observation and reading tests. The results indicate that students still experience difficulties in recognizing consonants, distinguishing similar letters, reading syllables, words, simple sentences, and understanding reading texts. The findings imply the need for intensive guidance from teachers and parents and regular reading practice.